2019
DOI: 10.1007/978-3-030-24907-6_18
|View full text |Cite
|
Sign up to set email alerts
|

An Encryption-Based Approach to Protect Fog Federations from Rogue Nodes

Abstract: People have used cloud computing approach to store their data remotely. As auspicious as this approach is, it brings forth many challenges: from data security to time latency issues with data computation as well as delivery to end users. Fog computing has emerged as an extension for cloud computing to bring data processing and storage close to end-users; however, it minimizes the time latency issue but still suffers from data security challenges. For instance, when a fog node providing services to end users is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Their scheme discovers the rogue AP by calculating the round-trip time between end-users and the DNS server. Mohammed et al [32] proposed an encryptionbased approach to protect fog computing from rogue fog nodes based on the CP-ABE algorithm. In this scheme, fog nodes cannot exchange data unless they fully trust each other.…”
Section: Rogue Fog Nodesmentioning
confidence: 99%
“…Their scheme discovers the rogue AP by calculating the round-trip time between end-users and the DNS server. Mohammed et al [32] proposed an encryptionbased approach to protect fog computing from rogue fog nodes based on the CP-ABE algorithm. In this scheme, fog nodes cannot exchange data unless they fully trust each other.…”
Section: Rogue Fog Nodesmentioning
confidence: 99%
“…Although this central point of failure issue can be mitigated by means of distributed approaches, this raises the issue of how to detect and counter rogue nodes within the network. In this line, we are building upon some of the latest developments in the security literature [25], along with our own work on handling behaviour deviations in complex networks for other domains [18,16,19].…”
Section: Implementation Of the Reshaping Frameworkmentioning
confidence: 99%
“…The project aims to help users extend their infrastructures, and easily get access to private computational resources using FC through simple GUI. Authors of [62] suggested adding the BC to their previously-proposed approach in [73], for protecting fog-enabled systems from malicious nodes. BC was deployed in this approach for delivering two services: data management and data access control.…”
Section: F Other Fc-bc Applicationsmentioning
confidence: 99%